Pengungkapan Environmental, Social, And Governance (ESG): Analisis Bibliometrik dan Agenda Penelitian Masa Depan (2013 – 2024) - Savirna Ulfa Cahyani Putri; Riten Sumarni; Dilla Diniya; Aditya Saputra; Laili Abdillah Ishak; Nofi Pauno (Jurnal Ilmu Sosial dan Humaniora, 2026)
The disclosure of Environmental, Social, and Governance (ESG) has become a crucial aspect of modern business due to increasing demands for transparency and sustainability. The development of international regulations such as GRI, TCFD, IFRS S1/S2, and CSRD has significantly driven ESG research. However, the rapid growth of literature has led to thematic fragmentation, necessitating a comprehensive mapping of ESG studies. This study aims to analyze publication trends, identify dominant themes, and map the intellectual development of ESG research from 2013 to 2024. A bibliometric analysis was conducted using performance analysis and science mapping approaches. Data were sourced from the Scopus database following the PRISMA protocol. From an initial 2,119 documents, filtering yielded 97 articles, which were analyzed using VOSviewer and Biblioshiny. Findings reveal a significant increase in ESG publications, particularly after 2018. The most dominant theme is ESG Disclosure and Reporting (29 articles), followed by Corporate Governance and ESG (21 articles), ESG and Financial Performance (18 articles), and others. Keyword network analysis shows ESG as a central concept linked to disclosure, firm value, CSR, and sustainable finance. Trend visualizations indicate a shift in focus from environmental issues toward governance and sustainable investment. This study provides theoretical and practical contributions for firms, investors, and regulators. Future research should expand database coverage and combine bibliometric analysis with qualitative approaches.